Art of the incarcerated: Art-making in the Japanese American Internment Camps. Issue 2 (1st June 2016) - Wenger, Gina Mumma
Researching histories of art education involves investigating a complex combination of documents, people, places and objects. Slowly, through time, histories evolve and the authors who document the narrative change. In this paper I strive to connect two significant material culture collections. One was gathered by an art teacher, Jamie Vogel, and created by high-school students during their incarceration in World War II Japanese American Internment Camps at Rohwer, Arkansas. The other comes from the recent debate over a collection of objects on the auction block from the Rago Arts and Auction Center. The items to be auctioned included several hundred donated examples of arts and crafts by Japanese and Korean American internees during World War II. They were donated to Allen Eaton and published in the 1952 book, Beauty Behind Barbed Wire: The Arts of the Japanese in Our War Relocation Camps. The stories, including the documentation surrounding these objects of material culture, enable conversations. Through the reflections of the collectors and those who contributed to them, we gain a broader understanding of the value of art-making and a critical view of dominant historical narratives.